Abrasive Jet Cutting in Flammable Atmospheres - Potential Applications for Mining - Fairhurst RM (The Australasian Institute of Mining and Metallurgy, 1985)
High pressure abrasive water jets have been shown capable of cutting a wide range of materials including steel, stone, rock and concrete. Acceptable performance can be achieved using relatively low pressures and expendable abrasives. The cutting head can be made small and abrasive feed systems have been developed that allow reliable pumping of slurries over long distances to supply such cutting heads. These features make abrasive water jets ideally suited to automated control in remote areas.Another major advantage of abrasive entraining water jet cutting heads is that they may be operated safely in potentially explosive environments due to their cold cutting ability. Therefore there are many possible applications for such equipment in mining.This paper gives an introduction to the abrasive water jet process and includes results of trials carried out at BHRA on a range of hard materials. Work is also described which investigated the operational safety of abrasive water jets in explosive environ-ments. In a special environmental chamber, cuts were made on steel and sandstone with atmospheres of methane/air and hydrogen/air, without caypsing ignition.